Histopathological findings of Endoscopic Gastric Biopsies of Patients attending a Tertiary Care Hospital - Rajendra Maharjan (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Chronic gastritis, is an inflammatory condition of the gastric mucosa, which can affect various parts of the stomach, causing degrees of mucosal damage. The purpose of this study was to find out the prevalence of histopathological findings of gastric mucosal biopsies among patients at a tertiary care hospital. Materials and Methods: A descriptive cross-sectional study was done among outpatients from January 9, 2017, to June 8, 2018, along with ethical approval from the Institutional Review Committee (Reference number: 12252016). Biopsy samples were collected from the antral mucosa, corpus, and angularis incisura mucosa of patients who underwent upper gastrointestinal endoscopies. Socio-demographic details and histopathological findings were noted. Convenience sampling was utilized, and the point estimate and 95% Confidence Interval were calculated. Results: Among 385 hospital-visiting patients, 80 (20.78%) had histopathological abnormalities (19.14-22.42, 95% Confidence Interval) with mean age of 69.90±15.32 years. Among patient with histopathological findings, eighty patients (100%) had dyspepsia, and 29 (36.30%) had ulcers findings on endoscopy, with higher prevalence in males and those aged 61-70 years. Provisional endoscopic diagnosis showed malignancies in 32 (40.00%) patients, but histopathological diagnosis revealed chronic gastritis in 40 (50.00%) patients. Conclusion: In patients who had undergone histopathological assessment, dyspepsia was frequently diagnosed by endoscopy, but chronic gastritis on histopathological assessment, most commonly in men and older adults.